SISTEM PEMIDANAAN LEMBAGA PEMASYARAKATAN KLAS IIB KABUPATEN TUBAN DIHIBUNGKAN DENGAN UNDANG-UNDANG NOMOR 12 TAHUN 1995 TENTANG PEMASYARAKATAN - Hariyo Sulistiyantoro (Fakultas Hukum, Universitas Islam Bandung, 2011)
A correctional institution is concerned with improving the behavior of criminals, usually by punishing them. It has a very important role in the effort to restore the prisoners into society. As part of the correctional institution program, coaching is designed to correct the behavior of criminals in order to prevent them from committing a crime again. More importantly, coaching is not intended to make them suffering, and to abandon their human rights. The aim of this article is to give a brief overview of the correctional institution criminal system in Penitentiary Class IIB of Tuban District under Law No.12 of 1995 on Penitentiary . In general, there are two approaches in conducting coaching pattern used by this Correctional Institution, namely by providing general coaching such as religious teaching, civic duties, intellectual capacity building and the raising of legal awareness. The Institution also provides technical coaching like self-reliance building that is realized by providing various skills that are tailored to the needs of the prisoners. It should be pointed out, however, that these prisoner rights are retained subject to requirements set out in the existing laws and regulation. The author concludes that although the provisions of Law No.12 of 1995 on Penitentiary are adequate to deal with the matters, Ministry of Justice and Human Rights should conduct a monitoring task in the law enforcement . Action can be taken to address the incompletenss of the current legislation on penitentiary.